Distribution and Stability of Soil Aggregates under Tree-based Cropping Systems in Sub-mountaneous Zone of Punjab, India - and Sandeep Sharma, Jeevanjot Dhaliwal, S.S. Kukal (Journal of the Indian Society of Soil Science, 2017)
Soil aggregate stability is a key indicator of soil structure. A study was conducted in sub-mountaneous region of Punjab to assess soil aggregation (dry and wet aggregate stability) under a maize-wheat cropping system in comparison to tree-based (agroforestry and agrihorticulture) systems. Results reveal that the distribution of dry stable aggregates (DSA) in both surface (0-15 cm) and sub-surface (15-30 cm) soil layers were similar under all systems, but the water stable macro-aggregates were dominant in soils under agroforestry. However, water stable micro-aggregates were dominant in soils under maize-wheat cropping system. The average mean weight diameter (MWD) of water stable aggregates (WSA) was highest (2.33 mm) in soils under agroforestry, followed by agrihorticulture (1.49 mm) and was lowest in soils under maize-wheat (0.78 mm). The mean stability index (SI), as measured by simulated single raindrop technique, followed similar trend to that of the MWD, being highest (0.135 J kg-1) in agroforestry followed by agrihorticulture (0.095 J kg-1) and was lowest (0.080 J kg-1) in maize-wheat. The proportion of water stable macro-aggregates was higher in soils under tree-based cropping systems in comparison to maize-wheat system. The soil structural stability in both the soil layers as indicated by MWD and SI was also higher in soils under tree-based cropping systems.